Neuronal Voltage Gated Potassium Channels May Modulate Nitric Oxide Synthesis in Corpus Cavernosum - Amira M. Senbel; Heba M. Abd Elmoneim; Fouad M. Sharabi; Mahmoud M. Mohy El-Din (Frontiers Media S.A., 2017)
Potassium channels (K+Ch) in corpus cavernosum play an important role in the regulation of erection. Nitric oxide (NO) acts through opening of K+Ch leading to hyperpolarization and relaxation.Aim : This study aims to update knowledge about the role of voltage-gated K+Ch (KV) channels in erectile machinery and investigate their role in the control of NO action &/or synthesis in the corpus cavernosum.Methods : Tension studies using isolated rabbit corpus cavernosum (CC) strips and rat anococcygeus muscle were conducted. Results are expressed as mean ± SEM.Results : Electric field stimulation (EFS, 2-16 Hz) evoked frequency-dependent relaxations of the PE (phenylephrine)-precontracted CC strips. At 2 Hz, EFS-induced relaxation amounted to 73.17 ± 2.55% in presence 4-AP (10−3 M) compared to 41.98 ± 1.45% as control. None of the other selective K+Ch blockers tested inhibited EFS-induced relaxation. 4-AP (10−3M) significantly attenuated ACh-induced relaxation of rabbit CC where dose-response curve was clearly shifted upward, and attenuated SNP- induced relaxation, for example, to 49.28 ± 4.52% compared to 65.53 ± 3.01% as control at 10−6 M SNP. The potentiatory effect of 4-AP on EFS was abolished or reversed in presence of NG-nitro-L-arginine (L-NNA, non-selective nitric oxide synthase inhibitor, 10−5M, and 2 × 10−4M). Same results were observed in rat anococcygeus muscle which is a part of the erectile machinery in rats.Conclusion : This study provides evidence for the presence of prejunctional voltage-gated K+Ch in CC, the blockade of which may increase the neuronal synthesis of NO.